2015
DOI: 10.1589/jpts.27.3185
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a new telerehabilitation system based on VR technology using multisensory feedback for patients with stroke

Abstract: [Purpose] The purpose of this study was to develop a new telerehabilitation system based on VR technology for training of paralyzed upper and lower extremities and poor balance in patients with stroke. Moreover, the effectiveness of the system was verified by analysis of the recovery of these patients. [Subjects] Five healthy persons and five people with motor paralysis, caused by cerebrovascular disease, participated. [Methods] The features of our system are as follows: (1) Our system can train upper and lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…It is proposed that this integrated somatosensory–motor retraining approach could optimize processes that drive reorganization of brain activation and neural connectivity to a greater extent leading to maximal functional improvement in the paretic upper limb compared with training somatosensory and motor function sequentially, which might be a suboptimal approach to relearn functional movements. Therefore, in order to maximize improvement of functional movements such as RTG after stroke, it is considered essential to address key sensory systems involved in this task (Kato, Tanaka, Sugihara, & Shimizu, ). It should be noted that even though the COMPoSE intervention does not directly target proprioceptive training, the latter is inherent in the reach and grasp aspects of the task, and feedback is provided in part with the motor training.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that this integrated somatosensory–motor retraining approach could optimize processes that drive reorganization of brain activation and neural connectivity to a greater extent leading to maximal functional improvement in the paretic upper limb compared with training somatosensory and motor function sequentially, which might be a suboptimal approach to relearn functional movements. Therefore, in order to maximize improvement of functional movements such as RTG after stroke, it is considered essential to address key sensory systems involved in this task (Kato, Tanaka, Sugihara, & Shimizu, ). It should be noted that even though the COMPoSE intervention does not directly target proprioceptive training, the latter is inherent in the reach and grasp aspects of the task, and feedback is provided in part with the motor training.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the multisensory stimulation interventions were focused on sensory function rather than the way a given intervention directly impacts the restoration of motor function. Recently, a pilot study demonstrated the feasibility of a virtual reality-based approach utilizing multisensory feedback during movement to improve motor function (Kato et al, 2015). Although encouraging, the pilot nature of this investigation precludes definitive conclusions regarding the benefits of multisensory approaches in stroke rehabilitation.…”
Section: Structural Approaches To Study the Pathology Of The Somatosementioning
confidence: 96%
“…Other single-valued quantities for progress have been previously proposed, yet the scale of progress remains difficult to quantify exactly. Some examples include time to accomplish the task (Yang and Kim, 2002;Kato et al, 2015), joint flexion/extension angle (Piqueras et al, 2013), and root mean square error between poses (Anderson et al, 2013). Our proposed Performance Score has two advantages over the aforementioned metrics.…”
Section: Augmented Feedbackmentioning
confidence: 99%
“…A VR example is the simulation of a 3D environment to facilitate arm-reaching exercises. This system also tracks users' joint positions, while vibratory feedback is given when task performance is successful (Kato et al, 2015). These systems use simple single-limb models to reduce the cognitive load on the patient and the computational load on the system.…”
Section: Introductionmentioning
confidence: 99%